2010
DOI: 10.1111/j.1939-1676.2010.0484.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Control of a Nosocomial Outbreak Caused by Salmonella Newport at a Large Animal Hospital

Abstract: Background: Nosocomial salmonellosis is often assumed to occur because infection control and surveillance practices are inadequate, but published evidence is lacking to support the related contention that rigorous application of these practices can impact the severity of outbreaks. Objective: Describe active surveillance, early recognition, and intensive mitigation efforts used in an effort to control an outbreak of nosocomial Salmonella enterica serotype Newport infections without hospital closure. Animals:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 18 publications
1
68
0
1
Order By: Relevance
“…Even though loads of recommendations for prevention and control of nosocomial infection is available out of the lesson learnt from previous experiences (Hartmann et al, 1996;Wright et al, 2005;Dallap et al, 2010;Goehring et al, 2010;Steneroden et al, 2010). Presently there is no recognized or published principles or standards for surveillance and control of infection in veterinary hospitals, which makes the system weak to determine rates and fraction of nosocomial and preventable infections respectively (Morley, 2002(Morley, , 2004Benedict et al, 2008;Morley and Weese, 2008).…”
Section: Surveillance In Veterinary Hospitalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though loads of recommendations for prevention and control of nosocomial infection is available out of the lesson learnt from previous experiences (Hartmann et al, 1996;Wright et al, 2005;Dallap et al, 2010;Goehring et al, 2010;Steneroden et al, 2010). Presently there is no recognized or published principles or standards for surveillance and control of infection in veterinary hospitals, which makes the system weak to determine rates and fraction of nosocomial and preventable infections respectively (Morley, 2002(Morley, , 2004Benedict et al, 2008;Morley and Weese, 2008).…”
Section: Surveillance In Veterinary Hospitalsmentioning
confidence: 99%
“…Studies have reported 1% to 5% prevalence of the sub-clinical shedding of Salmonella by horses entering veterinary clinics (Roberts and O'Boyle, 1981). Persistence of Salmonella in the hospital environment has been often reported to be associated with nosocomial outbreaks (Steneroden et al, 2010;) and environmental contamination with S. enterica in veterinary hospitals are identified as a hazard related to the nosocomial infections (Pandya et al, 2009;). In fact, many nosocomial outbreaks recorded in equine veterinary hospitals have been associated with multi drug resistant strains (Table 1).…”
Section: Salmonellamentioning
confidence: 99%
See 3 more Smart Citations